Republic of Tajikistan Public Sector Pay Reform : Policy Note on Medium-Term Pay Reform in Public Sector, Volume 2. Background Note - World Bank (Washington, DC, 2014)
This part of the public sector pay reform policy note represents a summary of main messages and findings of the report. The report also provides the summary of simulations for various policy scenarios; it is not imperative that quantitative parameters of policy actions (for example, base pay levels, etc.) should be exactly the same as in the policy note, actual numbers may change depending on available fiscal space by the time when final decision is taken vis-a-vis pay increase. Summary of recommendations is provided in annex two; by the time when the report was ready for publication, the Government already took actions to address immediate objectives of the pay reform agenda in public sector; it issued a decree to increase pay levels for civil servants, education and health sector workers as well as other social sector workers. In general, the decree was consistent with overall immediate objectives of pay reform in public service. Public sector wage reform is a key aspect of the reform agenda in Tajikistan. The strong erosion of real wages, as a consequence of the civil war and the collapse of the economy in the 1990s, and very limited employment opportunities in the country combined with increasing opportunities for labor migration, as a consequence of growing economies in Kazakhstan and Russia, have led to a large outflow of qualified personnel in the public service. At the same time, these sectors are crucial to the achievement of Millennium Development Goals (MDGs) and for ensuring sustainable growth. The public sector continued to provide a quarter of employment (25 percent) over the last seven years. Job creation in the economy was very marginal. It is very likely that the public sector will continue be one of the major employers in the local labor market in medium term. The policy note focuses on civil service, education, health, social protection, science, culture, and sport, sectors with a very uneven reform background and different starting points. The policy note attaches special emphasis on state of play in these sectors and explores options that could encompass policy decisions of the authorities in a three- to five-year timeframe.